Challenges of the application of PCMs to achieve zero energy buildings under hot weather conditions: A review. (1st August 2023) - Zahir, Md. Hasan; Irshad, Kashif; Shafiullah, Md; Ibrahim, Nasiru I.; Kausarul Islam, A.K.M.; Mohaisen, Khaled Own; Sulaiman, Fahad A.Al.
Abstract: With the global increase in population and temperature, cooling demand has increased tremendously in the building sector, especially in the GCC and African and South Asian countries where temperature can reach 50 °C from mid-May to August. Thermal performance of buildings can be effectively improved by using thermal energy storage (TES) systems based on phase change materials (PCMs). As PCMs melt during the daytime and solidify at nighttime, they can prevent rooms from overheating during daytime in hot months and may also reduce the need for heating during nighttime in the winter. This paper discusses the use of TES for the storage of sensible heat, latent heat, and thermochemical energy in buildings. Sustainable heating and cooling in buildings employing TES can be achieved with passive building envelope systems, active systems containing PCMs, sorption systems, and seasonal storage systems. This review presents results obtained in earlier studies on the incorporation of PCMs in building materials, the problems associated with the selection of PCMs, and various methods used to encapsulate PCMs for space heating and cooling applications. Furthermore, this article provides an outline of a range of PCM applications in buildings for decreasing the cooling loads under hot atmosphere conditions, and the parameters influencing the productive and viable use of PCMs under hot weather conditions. Several shortcomings in the application of PCMs, mostly due to the extreme summer weather conditions preventing the PCM from completely solidifying at night and thereby decreasing its effectiveness during the day, were identified. Although sunlight is abundant in the Middle East, the use of solar energy in conjunction with PCM technology for temperature control in buildings is rare. One of the main reasons for the status quo is the small temperature difference between day and night. Hence, the selection of a suitable PCM is crucial and challenging for this type of a hot atmosphere. As a consequence, the current study will fill a scientific gap concerning PCM usage in this vital hot temperature range. Under such extreme environmental conditions, thermal conductivity, density, and the specific heat of the insulation affect the heat flow. Finally, future research opportunities were explored and shortcomings of the technology as of today were discussed. Highlights: PCM uses for reducing cooling loads in buildings under hot climate conditions. Selection of a suitable PCM is crucial and challenging for a hot atmosphere. The potential for future research was explored, and the limitations were discussed.